Indexing of planned investments in the EES - Stanković, Miroslav P; Minić, Saša; Belić, Igor; Joković, Vladimir (Proceedings, Electrical engineering institute "Nikola Tesla", 2018)
The studies of planning development EES provide a set of solutions (investments) that need to be implemented in a period of time and for which it is necessary to allocate funds, that operate the system function within technically permissible limits. The proposed investments need to be ranked (indexed) at each stage of the planning period, in order to separate the most important ones. Four groups of investments have been formed, which have been prioritized for the realization. Within each investment group it is necessary to calculate a single index (weight) on the basis of which the investments will be ranked. In order to calculate the index (weights) within each investment group, a methodology has been formed. The final outcome of the applied methodology is the subset of the investments of each stage of a perspective period, formed on the basis of the rank of priorities.